Selective STAT3 Inhibitor Alantolactone Ameliorates Osteoarthritis via Regulating Chondrocyte Autophagy and Cartilage Homeostasis - Pei, Wenbin; Huang, Xiaojian; Ni, Bowei; Zhang, Rui; Niu, Guangyi; You, Hongbo (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA), which is identified by chronic pain, impacts the quality of life. Cartilage degradation and inflammation are the most relevant aspects involved in its development. Signal transducer and activator of transcription 3(STAT3), a member of the STATs protein family, is associated with inflammation. Alantolactone (ALT), a sesquiterpene lactone compound, can selectively suppress the phosphorylation of STAT3. However, the pharmacological effect of ALT on OA is still imprecise. In this study, IL-1β (10 ng/ml) was applied to cartilage chondrocytes, which were treated with different concentrations of Alantolactone for 24 hours. The expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2(COX2), matrix metalloproteinases (MMPs) and thrombospondin motifs-5 (ADAMTS5) were detected by western blot. Protein expression of Collagen Ⅱ was observed by western blot, safranin O staining and immunofluorescence. Manifestation of autophagy related proteins such as autophagy-related gene-5(ATG5), P62, LC3Ⅱ/Ⅰ and PI3K/AKT/mTOR-related signaling molecules were measured by western blot and autophagic flux monitored by confocal microscopy. Expression of STAT3 and NF-κB-related signaling molecules were evaluated by western blot and immunofluorescence. In vivo, 2mg/kg ALT or equal bulk of vehicle was engaged in the destabilization of medial meniscus (DMM) mouse models by intra-articular injection, the degree of cartilage destruction was classified by Safranin O/Fast green staining. Our findings reported that the enhance of inflammatory factors containing iNOS, COX2, MMPs and ADAMTS5 induced by IL-1β could be ameliorated by ALT. Additionally, the diminish of Collagen Ⅱ and autophagy which was stimulated by IL-1β could be alleviated by ALT. Mechanistically, STAT3, NF-κB and PI3K/AKT/mTOR signal pathways might be involved in the effect of ALT on IL-1β-induced mouse chondrocytes. In vivo, ALT protected cartilage in the DMM mouse model. Overall, this study illustrated that ALT attenuated IL-1β-induced inflammatory responses, relieved cartilage degeneration and promoted impaired autophagy via restraining of STAT3 and NF-κB signal pathways, implying its auspicious therapeutical effect for OA.